GROWTH AND FEEDING PATTERN IN CHILDRENS - Dr. Archana Kumari Anand, (EPRA International Journal of Research and Development (IJRD), 2022)
Breast feeding is more than just feeding and breast milk is more than just a food. Breast milk contains all the nutrients a healthy baby needs. It is a food produced by the mother's body especially for the baby. Breast milk is also rich in anti - infective substances and provides the baby with the best protection against diseases. Breast feeding is important for the healthy growth and development of all babies and creates a unique bond between mother and baby. When the mother breast feeds and holds her baby close she gives warmth, affection and security, as well as food and protection. Breast feeding is important for healthy growth and development of all babies. They need appropriate nutrition, affection, stimulation and protection against infection. Breast feeding meets these needs and gives them the best start in life. It is natural and a basic part of the life process.